2017
DOI: 10.12973/eurasia.2017.01221a
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Family Context in Explaining Grit of Taiwanese High School Students

Abstract: Grit, one of the newly developed non-cognitive traits, encompasses the characteristics of perseverance and consistency of interest. Grit is associated with good academic performance, resilience, and well-being. To understand the nature of Grit in detail, this study probed the relationship between Grit and the widely-applied and well-established Big-Five personality. Family context plays a significant role in nurturing all aspects of personality traits. Accordingly, we examined two family-context variables, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Among 54 studies that examined the effect of overall grit on students’ academic achievement, more than half (35 studies) reported significant positive results (Akos & Kretchmar, ; Cosgrove et al, ; Duckworth & Quinn, ; Duckworth et al, ; Dumfart & Neubauer, ; Farroll, ; Hill, ; Huang & Zhu, ; B. C. Lee, ; Lee & Sohn, ; Li et al, ; Lin & Chang, ; Mason, ; Muenks et al, ; Sheehan, ; Strayhorn, ; Tovar‐García, ; Wang et al, ; Williams, ), whereas one study reported a significant negative result (Climer, ). Six studies reported mixed results (Al‐Mutawah & Fateel, ; Cross, ; Kelly et al, ; O'Neal et al, ; Pate et al, ; Rojas, ) and eight studies reported nonsignificant results (Batres, ; Bazelais, Lemay, & Doleck, ; Engel, ; Flanagan & Einarson, ; Palisoc et al, ; Saunders‐Scott et al, ; Smith, ; Zurlo, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 54 studies that examined the effect of overall grit on students’ academic achievement, more than half (35 studies) reported significant positive results (Akos & Kretchmar, ; Cosgrove et al, ; Duckworth & Quinn, ; Duckworth et al, ; Dumfart & Neubauer, ; Farroll, ; Hill, ; Huang & Zhu, ; B. C. Lee, ; Lee & Sohn, ; Li et al, ; Lin & Chang, ; Mason, ; Muenks et al, ; Sheehan, ; Strayhorn, ; Tovar‐García, ; Wang et al, ; Williams, ), whereas one study reported a significant negative result (Climer, ). Six studies reported mixed results (Al‐Mutawah & Fateel, ; Cross, ; Kelly et al, ; O'Neal et al, ; Pate et al, ; Rojas, ) and eight studies reported nonsignificant results (Batres, ; Bazelais, Lemay, & Doleck, ; Engel, ; Flanagan & Einarson, ; Palisoc et al, ; Saunders‐Scott et al, ; Smith, ; Zurlo, ).…”
Section: Resultsmentioning
confidence: 99%
“…Among 31 studies that examined the effect of consistency of interest on students' academic achievement, 12 reported significant positive results (Hodge et al, 2018;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks, Yang, & Wigfield, 2018;Rimfeld, Kovas, Dale, & Plomin, 2016;Sheehan, 2014;Williams, 2017), 11 reported nonsignificant results (Akos & Kretchmar, 2017;Dixson, Roberson, & Worrell, 2017;Dixson, Worrell, Olszewski-Kubilius, & Subotnik, 2016;Hwang et al, 2017;W. Lee, 2017;MacCann & Roberts, 2010;Wolters & Hussain, 2015), and three reported mixed results (Kelly et al, 2014;Muenks et al, 2017;Steinmayr, Weidinger, & Wigfield, 2018).…”
Section: Consistency Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, [53] discovered the undergraduate students' GPA was forecasted by the self-report grit total score, and [49] stated that the high academic performance of student pharmacists in America was predicted by grit-total score. [54] students in Taiwan who have strong grit self-report higher academic performance and are more satisfied academically.…”
Section: Grit and Academic Achievementmentioning
confidence: 99%
“…M. Christopoulou et al Lin & Chang (2017) To explore the relationship between grit and academic performance and satisfaction, and to examine whether personality, family influence, and democratic parenting style predict grit.…”
Section: Correlation Hierarchical Multiple Regressionmentioning
confidence: 99%